Sustainability pedagogy: Understanding, exploring and internalizing nature’s complexity and coherence - Spiegelaar, Nicole (Frontiers in Psychology, 2023)
Online learning during the COVID-19 pandemic has affected student academic performance as well as mental, physical, and social wellbeing. During a lockdown at the University of Toronto in Canada (September 2020–April 2021), my students expressed an underlying sense of monotony yet uncertainty. I recalled a contrasting paradox from the teachings of Indigenous Cree on mental wellness in land-based experiences: a sense of stimulation and security that we can liken to variations of Appleton’s prospect-refuge theory. I modified my Environmental Science and Pathways to Sustainability course to support stimulation and security through embodied, interactive pedagogy at student-selected individual field sites. My main goals were to (i) support student mental wellness and (ii) provide an alternative to experiential field trips for understanding and connecting with nature as an adaptive complex system. I prompted students with field activities contextualized by a course narrative that purposefully directed attention to nature through intrinsically motivated curiosity, exploration, and discovery; conditions more similar to evolutionary environments of adaptedness than “getting away” in passive retreats. Student weekly field observations and reflections culminated in a post-intervention Reflection Assignment (n = 15) which became the bases of thematic and narrative analysis. Other assignments were added to my evaluation of complexity comprehension. The intervention successfully instilled security and stimulation via purpose-directed attention to different aspects of nature in the same setting followed by periods of knowledge integration. This empowered students with sustainability mindsets indicated by greater self-reported: sense of coherence, change agency, cognitive and affective restoration, nature connectedness, nature relatedness, social connectedness, and pro-environmental values. Assignments demonstrated an understanding of the environment as an adaptive complex system that was not present at the beginning of the course. Some students’ self-construct adopted nature and its complexity, empowering them with greater trait resilience. This work speaks to opportunities for merging psychological restoration and analytical curricula by integrating cognitive and sensory meaningfulness in sustainability narratives. It asks scholars to reflect on how we operationalize foundational theories of Environmental Psychology based on ancestral survival conditions and encourages empirical research to consider how sociocultural contexts can direct attention to nature through purposeful inquiry.